2017
DOI: 10.17951/aa.2017.72.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Stability of colloidal systems - a review of the stability measurements methods

Abstract: <p>The stability of colloidal systems is very important in numerous already existing and new formulations. In most cases if such systems are not characterized by an appropriate stability they can not find any useful applications. The opposite process to the stabilization is the flocculation. Generally, it is undesirable. However, in a few cases the flocculation is very useful, for example in  the wastewater treatment. That is why the methods used to determine stabilizing-flocculating properties of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The higher conductivities (up to 181% increase) of the Cu 2 O–polysaccharide complexes versus the native polysaccharide were probably due to the higher number of charged particles (Cu ions and polysaccharide). Our results showed that the native polysaccharide and the Cu 2 O–polysaccharide complexes exhibited similar values of the zeta potential (range of −45 to −49 mV), implying good stability and probable complexation of Cu ions into the polysaccharide. The zeta potential of the Cu 2 O solutions (250/500/750 ppm Cu in buffer, pH 4.5) ranged from +20.5 to +22.9 as was previously described by Guillaume Salek et al In addition, cyclic voltammetry analysis (Figure S1) of the Cu 2 O–polysaccharide complex showed that the oxidation state of copper does not change while in the complex, as was previously indicated .…”
Section: Resultssupporting
confidence: 78%
“…The higher conductivities (up to 181% increase) of the Cu 2 O–polysaccharide complexes versus the native polysaccharide were probably due to the higher number of charged particles (Cu ions and polysaccharide). Our results showed that the native polysaccharide and the Cu 2 O–polysaccharide complexes exhibited similar values of the zeta potential (range of −45 to −49 mV), implying good stability and probable complexation of Cu ions into the polysaccharide. The zeta potential of the Cu 2 O solutions (250/500/750 ppm Cu in buffer, pH 4.5) ranged from +20.5 to +22.9 as was previously described by Guillaume Salek et al In addition, cyclic voltammetry analysis (Figure S1) of the Cu 2 O–polysaccharide complex showed that the oxidation state of copper does not change while in the complex, as was previously indicated .…”
Section: Resultssupporting
confidence: 78%
“…Since, zeta potential is dependent on the orientation of slipping planes and on the chemical constituents, therefore, the decrease in zeta potential means that the attraction forces between the surface and the slipping plane are reduced. 55 This might be due to the interactions of the surface of NPs and with the H + and OH − ions present in the system.…”
Section: Resultsmentioning
confidence: 99%
“…This is a dimensionless indicator that allows one to compare the samples with each other and can vary in the range of 0-100. The value of the TSI is inversely proportional to the system stability [49]. The Turbiscan brochure states that up to the Turbiscan Stability Index equal to 1, the system is stable (referred to as Visually Excellent for TSI < 0.5 or Visually Good for TSI < 1.0).…”
Section: Resultsmentioning
confidence: 99%